2016
DOI: 10.18293/seke2016-010
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analyzing Security Patterns Using High Level Petri Nets

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…He and Fu [22] modelled and analysed six security patterns, namely, account lockout, authenticated session, client data storage, encrypted storage, password authentication, and password propagation, to check their completeness, consistency, and ambiguity in their textual descriptions. He and Fu [22] used high-level petri nets to ensure the correct implementation of these six security patterns.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…He and Fu [22] modelled and analysed six security patterns, namely, account lockout, authenticated session, client data storage, encrypted storage, password authentication, and password propagation, to check their completeness, consistency, and ambiguity in their textual descriptions. He and Fu [22] used high-level petri nets to ensure the correct implementation of these six security patterns.…”
Section: Related Workmentioning
confidence: 99%
“…He and Fu [22] modelled and analysed six security patterns, namely, account lockout, authenticated session, client data storage, encrypted storage, password authentication, and password propagation, to check their completeness, consistency, and ambiguity in their textual descriptions. He and Fu [22] used high-level petri nets to ensure the correct implementation of these six security patterns. Near and Jackson [23] showed that previously unknown security bugs could be easily identified using their proposed formal approach SPACE (Security Pattern Checker), which finds implementation bugs in access control security patterns.…”
Section: Related Workmentioning
confidence: 99%
“…Five security patterns were studied. • using High Level Petri-nets [16] and Colored Petri-nets [17] to model security patterns and to combine security patterns with existing models [11], [12]. The above works either focus on the individual security patterns or treat the composition of security patterns as a whole system.…”
Section: A Verification Of Security Patternsmentioning
confidence: 99%
“…5), including Ambient Intelligence Environments, Business Process Management (BPM), and Multi-Agent Systems (MAS). Most reports use general platforms like the web, cloud, and distributed system.A few papers address Cyber Physical Systems (CPS) and the Internet of Things (IoT)[227,233]. However, various IoT security patterns are emerging.…”
mentioning
confidence: 99%